Intrastrain genomic and phenotypic variability of the commercial Saccharomyces cerevisiae strain Zymaflore VL1 reveals microevolutionary adaptation to vineyard environments - Franco-Duarte, Ricardo
The maintenance of microbial species in different environmental conditions is associated with adaptive microevolutionary changes that are shown here to occur within the descendants of the same strain in comparison with the commercial reference strain. However, scarce information is available regarding changes that occur among strain descendants during their persistence in nature. Herein we evaluate genome variations among four isolates of the commercial winemaking strain Saccharomyces cerevisiae Zymaflore VL1 that were re-isolated from vineyards surrounding wineries where this strain was applied during several years, in comparison with the commercial reference strain. Comparative genome hybridization showed amplification of 14 genes among the recovered isolates being related with mitosis, meiosis, lysine biosynthesis, galactose and asparagine catabolism, besides 9 Ty elements. The occurrence of microevolutionary changes was supported by DNA sequencing that revealed 339–427 SNPs and 12–62 indels. Phenotypic screening and metabolic profiles also distinguished the recovered isolates from the reference strain. We herein show that the transition from nutrient-rich musts to nutritionally scarce natural environments induces adaptive responses and microevolutionary changes promoted by Ty elements and by nucleotide polymorphisms that were not detected in the reference strain.